Identification of Small Inhibitory Molecules Targeting the Bfl-1 Anti-Apoptotic Protein That Alleviates Resistance to ABT-737. (August 2014) - Mathieu, Anne-Laure; Sperandio, Olivier; Pottiez, Virginie; Balzarin, Sophie; Herlédan, Adrien; Elkaïm, Judith O.; Fogeron, Marie-Laure; Piveteau, Catherine; Dassonneville, Sandrine; Deprez, Benoit; Villoutreix, Bruno O.; Bonnefoy, Nathalie; et al.
One approach currently being developed in anticancer drug discovery is to search for small compounds capable of occupying and blocking the hydrophobic pocket of anti-apoptotic Bcl-2 family members necessary for interacting with pro-apoptotic proteins. Such an approach led to the discovery of several compounds, such as ABT-737 (which interacts with Bcl-2, Bcl-xl, and Bcl-w) or the latest one, ABT-199, that selectively targets Bcl-2 protein. The efficacy of those compounds is, however, limited by the expression of two other anti-apoptotic Bcl-2 members, Mcl-1 and Bfl-1. Based on the role of Bfl-1 in cancer, especially in chemoresistance associated with its overexpression in B-cell malignancies, we searched for modulators of protein–protein interaction through a high-throughput screening of a designed chemical library with relaxed drug-like properties to identify small molecules targeting Bfl-1 anti-apoptotic protein. We found two compounds that display electrophilic functions, interact with Bfl-1, inhibit Bfl-1 protective activity, and promote cell death of malignant B cells. Of particular interest, we observed a synergistic effect of those compounds with ABT-737 in Bfl-1 overexpressing lymphoma cell lines. Our results provide the basis for the development of Bfl-1 specific antagonists for antitumor therapies.